Comparison of the clinical utility of atrial and B type natriuretic peptide measurement for the diagnosis of systolic dysfunction in a low-risk population. Issue 5 (18th May 2007) - Galasko, Gavin; Collinson, Paul O; Barnes, Sophie C; Gaze, David; Lahiri, Arjivit; Senior, Roxy
Abstract : Background: Measurement of B type natriuretic peptide and its N terminal prohormone (NTproBNP) can now be performed routinely by automated high-throughput immunoassays. The study compared measurement of NTproBNP with measurement of N terminal pro-atrial natriuretic peptide (NTproANP) for detection of ventricular systolic dysfunction in primary care. Methods: 734 subjects aged >45 years (349 men and 385 women, median age 58 years, range 45–89, interquartile range 51–67 years) from seven representative general practices attended for echocardiography with determination of ejection fraction and completed a questionnaire. Blood samples were collected into gel serum separation tubes (Becton–Dickinson, Franklin Lakes, New Jersey, USA), the serum separated and aliquots stored frozen at −70°C until analyses. Samples were analysed for NTproBNP (Roche Diagnostics, Lewes, UK; coefficient of variation (CV) 3.2–2.4%) and for NTproANP (Biomedica, Vienna, Austria; CV 5.6–10.1%). Echocardiography was used as the diagnostic "gold standard", with ventricular systolic dysfunction defined as abnormal when there was an ejection fraction of ⩽40%. Patients were dichotomised by ejection fraction from 50% to 30%, and receiver operating characteristic curves constructed and the area under the curve (AUC) compared. Results: At 40% ejection fraction, NTproANP and NTproBNP showed AUCs of, respectively, 0.738 (0.601–0.875) and 0.973 (0.958–0.989), p<0.004. Conclusion: NTproBNP is superior to NTproANP for detection of systolic dysfunction.